Homocysteine predicts vascular target organ damage in hypertension and may serve as guidance for first‐line antihypertensive therapy - Revathy Carnagarin; Janis M. Nolde; Natalie C. Ward; Leslie Marisol Lugo‐Gavidia; Justine Chan; Sandi Robinson; Ancy Jose; Anu Joyson; Omar Azzam; Márcio Galindo Kiuchi; Bibombe P. Mwipatayi; Markus P. Schlaich (The Journal of Clinical Hypertension, 2021)
Abstract Homocysteine is an independent risk factor for cardiovascular and cerebrovascular disease and has been proposed to contribute to vascular dysfunction. We sought to determine in a real‐world clinical setting whether homocysteine levels were associated with hypertension mediated organ damage (HMOD) and could guide treatment choices in hypertension. We performed a cross‐sectional analysis of prospectively collected data in 145 hypertensive patients referred to our tertiary hypertension clinic at Royal Perth Hospital and analyzed the association of homocysteine with HMOD, renin‐angiotensin‐aldosterone system (RAAS), and RAAS blockade. The average age of participants was 56 ± 17 years, and there was a greater proportion of males than females (89 vs. 56). Regression analysis showed that homocysteine was significantly associated with PWV (β = 1.99; 95% CI 0.99‐3.0; p < .001), albumin‐creatinine ratio (lnACR: β = 1.14; 95% CI 0.47, 1.8; p < .001), 24 h urinary protein excretion (β = 0.7; 95% CI 0.48, 0.92; p < .001), and estimated glomerular filtration rate (β = −29.4; 95% CI −36.35, −22.4; p < .001), which persisted after adjusting for potential confounders such as age, sex, 24 h BP, inflammation, smoking, diabetes mellitus (DM), and dyslipidemia. A positive predictive relationship was observed between plasma homocysteine levels and PWV, with every 1.0 µmol/L increase in homocysteine associated with a 0.1 m/s increase in PWV. Homocysteine was significantly associated with elevated aldosterone concentration (β = 0.26; p < .001), and with attenuation of ACEi mediated systolic BP lowering and regression of HMOD compared to angiotensin receptor blockers in higher physiological ranges of homocysteine. Our results indicate that homocysteine is associated with hypertension mediated vascular damage and could potentially serve to guide first‐line antihypertensive therapy.